Interleukin-6 Perpetrator of the COVID-19 Cytokine Storm - Shekhawat, Jyoti (Indian J Clin Biochem, 2021)
COVID-19 has emerged as a global pandemic. It is mainly manifested as pneumonia which may deteriorate into severe respiratory failure. The major hallmark of the disease is the systemic inflammatory immune response characterized by Cytokine Storm (CS). CS is marked by elevated levels of inflammatory cytokines, mainly interleukin-6 (IL-6), IL-8, IL-10, tumour necrosis factor-α (TNF-α) and interferon-γ (IFN-γ). Of these, IL-6 is found to be significantly associated with higher mortality. IL-6 is also a robust marker for predicting disease prognosis and deterioration of clinical profile. In this review, the pivotal role played by IL-6 in the immuno-pathology of COVID-19 has been illustrated. The role of IL-6 as a pleiotropic cytokine executing both pro and anti-inflammatory activities has been reviewed. ADAM 10, a metalloproteinase switches the anti-inflammatory pathway of IL-6 to pro inflammatory hence blocking the action of ADAM 10 could be a new therapeutic strategy to mitigate the proinflammatory action of IL-6. Furthermore, we explore the role of anti-IL6 agents, IL-6 receptor antibodies which were being used for autoimmune diseases but now are being repurposed for the therapy of COVID-19.